Analysis of the competitiveness of the agricultural sector to the leading sector in Tebing Tinggi City - Ginting, Renata Olivia; Fahrani, Meuthia; Situmorang, Eva Juli Yanti (Outline Publisher, 2025)
This research analyzes the competitiveness of the agricultural sector in Tebing Tinggi City compared to other leading sectors using the Location Quotient (LQ) and Shift Share Analysis methods. The main focus is how the agricultural sector contributes to regional economic growth and its competitiveness compared to other sectors. The main finding is that the Basic Sector (LQ > 1) is several of Tebing Tinggi's leading sectors including educational services, government administration, construction, as well as investment and food and drink. These sectors show export potential and are the main drivers of the economy. Non-Basic Sector (LQ < 1) The agricultural sector has a low LQ (0.048), indicating that its contribution to the Tebing Tinggi economy is relatively small compared to the national level. Shift Share Analysis: The education, real estate and financial services sectors have faster growth than the national average, while agriculture shows slower growth. The agricultural sector in Tebing Tinggi City has not yet become the dominant sector in the economic structure, even though its potential is large. Strengthening technology, commodity diversification and increasing international market access are needed to increase the competitiveness of this sector.